Preserving Islamic Tradition in the E-Commerce Era: A Sharia Perspective on Affiliate Marketing - Asra, Moh. (UIN Syarif Hidayatullah Jakarta, 2025)
This research explores the role of affiliate marketing in preserving Islamic traditions within Indonesia's digital economy, particularly from the perspective of Sharia economic law. The problem addressed is the lack of clear guidance on Sharia compliance in modern affiliate practices, which are increasingly popular among the Muslim community. The study aims to identify how affiliate marketing can align with Islamic values and contribute to ethical digital commerce. Using a qualitative approach and literature study method, data were collected from journals, books, DSN-MUI fatwas, and relevant regulations. The findings reveal that affiliate marketing, although modern, can uphold core Sharia principles such as honesty (ṣiddiq), justice ('adālah), and responsibility (amanah). These values are crucial for avoiding unethical practices like gharar and deceit. The research concludes that affiliate marketing can serve as a medium for Islamic da'wah and economic empowerment if managed by Sharia. It recommends developing specific guidelines and promoting digital ethics through Islamic education.